Shifts in Fox Den Occupancy in the Greater Prudhoe Bay Area, Alaska - Stickney, Alice A.; Obritschkewitsch, Tim; Burgess, Robert M. (ARCTIC, 2014)
Although shifts in the distribution of red foxes into areas previously dominated by Arctic foxes have been documented over wide areas of the circumpolar North, no such documentation exists yet for the Alaskan Arctic. Fox research in the greater Prudhoe Bay area from the 1970s through the early 1990s focused primarily on Arctic foxes in relation to oil development because red foxes were uncommon. A monitoring program in 2005–12 included annual surveys of 31–48 fox dens within 2 km of the road system. In 2005, 2006, and 2008, Arctic fox dens outnumbered those of red foxes, but from 2010 onward, the reverse was true. There is greater distance between natal dens of Arctic foxes and those of red foxes than between natal dens within each species, suggesting that Arctic foxes avoid red fox denning territories. Of dens in our study that were used by Arctic foxes prior to 2005, 50% have since been occupied by red foxes. Red foxes displaced Arctic foxes from dens closest to oil field camps, pads, and other facilities, and preyed on their pups. Access to anthropogenic food sources probably supports red foxes in the area. Predictions from climate change studies indicate the displacement of Arctic foxes by red foxes will continue in the Alaskan Arctic, although the change may be slower away from areas of human occupation and anthropogenic foods. Malgré que des changements sur le plan de la répartition du renard roux dans des régions qui étaient auparavant dominées par le renard arctique aient été répertoriés dans une grande partie du Nord circumpolaire, ce n’est pas encore le cas de l’Arctique alaskien. L’étude des renards de la grande région de la baie Prudhoe, des années 1970 jusqu’au début des années 1990, portait principalement sur le renard arctique dans le cadre de la mise en valeur du pétrole, car le renard roux n’était pas courant à ce moment-là. Un programme de surveillance mené à bien de 2005 à 2012 a notamment pris la forme de dénombrements annuels de 31 à 48 tanières de renards dans un rayon de deux kilomètres ...